Reliability and Quality of Complex Systems - M.E. Danilin; A.V. Zayara (Надежность и качество сложных систем)
Background. Modern mobile robotics systems are equipped with complex electrical equipment, which accounts for more than half of failures due to degradation processes. The electrical equipment shall be monitored to identify its technical status. Materials and methods. To perform the monitoring tasks, a model of technical status change is proposed, on the basis of which an identification of the technical status is made using methods of unclear logical classification, nuclear density assessment and immediate neighbors. Results and conclusions. The improvement of diagnostic equipment in the area of forecasting using this model will permanently identify the technical status.